Synthesis of 1-Amino-2,5-dihydro-1H-phosphole 1-Oxides and Their N-Phosphinoyl Derivatives, Bis(2,5-dihydro-1H-phosphol-1-yl)amine P,P′-Dioxides - Kiss, Nóra Zsuzsa; Simon, András; Drahos, László; Huben, Krzysztof; Jankowski, Stefan; Keglevich, György (Synthesis, 2013)
Depending on the molar ratio of the reactants and on the order of mixing, the reactions of a series of primary amines with 1-chloro-2,5-dihydro-1H-phosphole 1-oxides prepared in situ from the corresponding hydroxy-dihydrophosphole oxides afforded 1-amino-2,5-dihydro-1H-phosphole 1-oxides, or their N-phosphinoyl derivatives, bis(2,5-dihydro-1H-phosphol-1-yl)amine P,P′-dioxides. The latter family of P-heterocycles could also be synthesized by the reaction of 1-amino-2,5-dihydro-1H-phosphole oxides with chloro-dihydrophosphole oxides.
Keywords: phosphorus; heterocycles; amides; phosphorylation; spectroscopy